2022
DOI: 10.53808/kus.2022.19.01.2119-edu
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Underlying Factors of Dropping Out at Secondary-Level Schools in Khulna, Bangladesh

Abstract: Despite a remarkable development in the education system in Bangladesh, the country still experiences a huge amount of dropout cases every year which is alarming. This study attempts to explore the whys and wherefores of dropping outs of the secondary-level students in the Khulna district. Apart from this, the research also investigates the current conditions of the dropped-out students. Quantitative and qualitative data have been collected from 52 dropouts who were selected using convenience sampling method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Shi and Lei (2021) found that upper-middle-class speakers exhibit more lexical richness than middle-class speakers, using quantitative lexical richness measures as part of their research on lexical indices to explore disparities in social class. In a study inquiring about the underlying factors of dropping out of secondary-level schools in Bangladesh, researchers identified parental negligence, financial crises, and no access to tuition among families of lower-class backgrounds (Sheikh et al, 2022). According to Black et al (2008), because adolescence is the first time that lexical usage gains public significance, there are no discernible distinctions between class and lexical use among preschoolers.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Shi and Lei (2021) found that upper-middle-class speakers exhibit more lexical richness than middle-class speakers, using quantitative lexical richness measures as part of their research on lexical indices to explore disparities in social class. In a study inquiring about the underlying factors of dropping out of secondary-level schools in Bangladesh, researchers identified parental negligence, financial crises, and no access to tuition among families of lower-class backgrounds (Sheikh et al, 2022). According to Black et al (2008), because adolescence is the first time that lexical usage gains public significance, there are no discernible distinctions between class and lexical use among preschoolers.…”
Section: Review Of Literaturementioning
confidence: 99%